First-line immune-based combinations or sunitinib in favorable-risk metastatic renal cell carcinoma: a real-world retrospective comparison from the ARON-1 study - Roviello, Giandomenico; Molina-Cerrillo, Javier; Massari, Francesco; Cerbone, Linda; Fiala, Ondrej; Fornarini, Giuseppe; Monteiro, Fernando Sabino Marques; Cattrini, Carlo; Landmesser, Johannes; Messina, Carlo; Zgura, Anca; Rebuzzi, Sara Elena; et al. (Cancer immunology, immunotherapy, 2025)
INTRODUCTION: Renal cell carcinoma (RCC) is one of the most common types of urogenital cancer. The introduction of immune-based combinations, including dual immune-checkpoint inhibitors (ICI) or ICI plus tyrosine kinase inhibitors (TKIs), has radically changed the treatment landscape for metastatic RCC, showing varying efficacy across different prognostic groups based on the International Metastatic RCC Database Consortium (IMDC) criteria. MATERIALS AND METHODS: This retrospective multicenter study, part of the ARON-1 project, aimed to evaluate the outcomes of favorable-risk metastatic RCC patients treated with immune-based combinations or sunitinib. Patients were assessed for overall survival (OS), progression-free survival (PFS) and overall response rate. We carried out a survival analysis by a Cox regression model. RESULTS: A total of 524 favorable-risk patients were included in the analysis. After a median follow-up of 37.2 months, the median OS in the overall population was 56.1 months. There was no significant difference in OS between patients receiving sunitinib and those receiving TKI + ICI combinations (p = 0.761). Patients on TKI + ICI had significantly longer PFS compared to patient treated with sunitinib (30.7 vs 22.9 months, p = 0.007). Analysis of OS and PFS based on metastatic site revealed that patients with bone metastases benefited more from ICI plus TKI (56 patients with bone metastases receiving IO + TKI, 38 received pembrolizumab plus axitinib, 15 cabozantinib plus nivolumab and 3 pembrolizumab plus lenvatinib), while sunitinib was more effective for pancreatic and glandular metastases. Additionally, the number of metastatic sites played a role, with TKI plus ICI showing superiority in patients with a single metastatic site. The time from RCC diagnosis to metastatic disease also impacted outcomes, with TKI plus ICI being more effective in patients with a shorter interval (i.e., < 36 months). CONCLUSIONS: The choice between upfront combination or monotherapy for metastatic favorable prognosis RCC remains a current issue. While combination therapy offers prolonged PFS, it does not necessarily translate to improve OS compared to sunitinib. This real-world study supports the superiority in terms of PFS of TKI plus ICI vs TKI monotherapy but not in OS. Probable, other clinical factors should be taking into account to make clinical treatment decisions in this setting.
Keywords: senioři; metastázy nádorů; Phenylurea Compounds; Carcinoma, Renal Cell; Quinolines; Sunitinib; Protein Kinase Inhibitors; Good favorable-risk IMDC criteria; Immune Checkpoint Inhibitors; Retrospective Studies; Prognosis; lidé; Middle Aged; mužské pohlaví; Pyridines; pyridiny; karcinom z renálních buněk; Adult; Renal cell carcinoma; ARON-1 study; sunitinib; Kidney Neoplasms; inhibitory kontrolních bodů; Neoplasm Metastasis; ženské pohlaví; prognóza; retrospektivní studie; Humans; lidé středního věku; Immune-based combinations; Antineoplastic Combined Chemotherapy Protocols; rizikové faktory; Immunotherapy; inhibitory proteinkinas; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Risk Factors; chinoliny; nádory ledvin; Male; fenylmočovinové sloučeniny